Illegal - Colfer, Eoin; Donkin, Andrew; Rigano, Giovanni; Dickey, Chris (Naperville, Illinois : Sourcebooks Jabberwocky, an imprint of Sourcebooks, Inc., 2018)
"Ebo is alone. His brother, Kwame, has disappeared, and Ebo knows it can only be to attempt the hazardous journey to Europe, and a better life, the same journey their sister set out on months ago. But Ebo refuses to be left behind in Ghana. He sets out after Kwame and joins him on the quest to reach Europe. Ebo's epic journey takes him across the Sahara Desert to the dangerous streets of Tripoli, and finally out to the merciless sea. But with every step he holds on to his hope for a new life, and a reunion with his family"--Provided by publisher.
Originally published in 2017 in Great Britain by Hodder Children's Books, an imprint of Hachette Children's Group, a part of Hodder & Stoughton.
Ages 10 and up.
Keywords: Unaccompanied immigrant children -- Europe -- Juvenile fiction; Unaccompanied refugee children -- Ghana -- Juvenile fiction; Noncitizen children -- Europe -- Juvenile fiction; Families -- Juvenile fiction; Unaccompanied immigrant children -- Europe -- Fiction; Unaccompanied refugee children -- Ghana -- Fiction; Illegal alien children -- Europe -- Fiction; Families -- Fiction